Effect of Red and Blue Light on Lipid, Protein, Carbohydrate, and Pigment Contents of Navicula sp. - Maulana, Sofyan; Nurul Hida, Aulia Setyo; Wulandari, Ismia; Mudrikah, Siti; Kurnianto, Dedy; Maghfiroh, Khusnul Qonita; Amelia, Ria; Erfianti, Tia; Putri, Renata Adaranyssa Egistha; Devi Anggraini, Irika; Marno, Septhian; Suyono, Eko Agus Agus (Makara Journal of Science, 2025)
Light quality critically modulates the physiology of diatoms, influencing photosynthetic efficiency and metabolite synthesis. This study examines how monochromatic red (620–750 nm) or blue (450–495 nm) light affects the biochemical profiles and pigment production in Navicula sp. versus white light (control). Cultures were grown in sterile f/2 medium, and biomass was tracked via OD680. Biochemical analyses included lipids (Bligh and Dyer method), carbohydrates (phenol-sulfuric acid assay), proteins (Bradford assay), and pigments (spectrophotometric quantification). The growth dynamics were modeled using logistic and Gompertz equations. No significant differences in OD-based growth rates, carbohydrates, proteins, or lipids content were observed with red or blue light compared with the control. However, blue light elevated chlorophyll a levels 4-fold and maximized protein productivity 3-fold, whereas red light enhanced carotenoid content by 20.5-fold. The growth kinetics modeling that best matched the experimental data was the Gompertz modeling (R² > 0.649). These results demonstrate the wavelength-specific regulation of pigment and protein yields, suggesting that tailored light regimes can selectively optimize high-value metabolites in Navicula sp. This approach holds promise for biotechnology sectors prioritizing targeted compound production, such as nutraceuticals or biofuels, by leveraging spectral tuning to enhance metabolic efficiency and predicting particular growth phases using growth kinetics.